2019
DOI: 10.3390/ijms20092236
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Cells, Stem Cells, and p53: Can We Stereotype p53 Functions?

Abstract: In recent years, great interest has been devoted to finding alternative sources for human stem cells which can be easily isolated, ideally without raising ethical objections. These stem cells should furthermore have a high proliferation rate and the ability to differentiate into all three germ layers. Amniotic fluid, ordinarily discarded as medical waste, is potentially such a novel source of stem cells, and these amniotic fluid derived stem cells are currently gaining a lot of attention. However, further info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The tumor protein p53 promotes apoptosis, independent of transcription via direct interaction with anti-apoptotic proteins. The activity of p53 is regulated by its protein abundance as well as by its posttranslational modifications [9]. This research aimed to assess the serum levels of apoptosis proteins in hyperthyroid patient's serum and study its association with the thyroid-related autoimmune antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor protein p53 promotes apoptosis, independent of transcription via direct interaction with anti-apoptotic proteins. The activity of p53 is regulated by its protein abundance as well as by its posttranslational modifications [9]. This research aimed to assess the serum levels of apoptosis proteins in hyperthyroid patient's serum and study its association with the thyroid-related autoimmune antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The most important step in the treatment of nonunion problems of broken bones is autologous bone grafting, in which bone fragments are taken from a secondary site and transferred to the fracture line in order to accelerate the healing process. Although autogenous bone grafting is accepted as the gold standard in bone healing, it can be faced with disadvantages such as morbidity in the donor area where the graft is taken and low quality autologous bone graft material [4,5]. Researchers have been developing alternative treatment methods for delayed fracture healing for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Amniotic fluid (AF) is a protective layer that keeps the foetus safe by providing mechanical support and supplying nutrients during embryogenesis. The major component of AF is water, although its cellular composition always changes during pregnancy ( 32 ). AF represents a nourishing source of the stem cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of isolation methods, all of them are positive for CD44, CD29, CD90, CD105, OCT4, NANOG and SSEA4 ( 34 ). AF-MSCs were in closer similarity to adult stem cells compared to ESCs and induced pluripotency stem cells (iPSCs) ( 32 ). Extensive studies have demonstrated that cell number obtained through amniocentesis is mostly affected by volume, variation of donors and gestational stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation